2023
DOI: 10.3390/min13081019
|View full text |Cite
|
Sign up to set email alerts
|

Palladian Gold: Chemical Composition, Minerals in Association, and Physicochemical Conditions of Formation at Different Types of Gold Deposits

Galina A. Palyanova,
Pavel S. Zhegunov,
Tatiana V. Beliaeva
et al.

Abstract: This paper reviews and summarizes the available information on the composition of palladian gold with various contents and sets of isomorphic impurities (Ag, Cu, Hg) at 50 deposits and ore occurrences with Au-Pd mineralization. It is revealed that Palladian gold is represented by the systems Au–Pd, Au–Pd–Hg, Au–Pd–Cu, and Au–Pd–Ag–Hg, but more frequently corresponds to Au–Pd–Ag, Au–Pd–Ag–Cu, and Au–Pd–Ag–Cu–Hg. Objects with palladian gold belong to different types of gold deposits and to the deposits at which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Identified patterns made it possible to develop a method for predicting minerogenic types of gold deposits based on the indicators of placer gold and features of their distribution and to link them with various geological structures for the first time [15]. Similar studies on the mineralogy of placer gold, in order to identify the types of ore sources and the genesis of placers, have been successfully conducted and continue to be developed by Russian scientists [16][17][18][19][20][21][22] and also by foreign researchers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The study of the typomorphic features of placer gold (morphology, chemical composition, micro-inclusions, internal structure) in order to identify minerogenic types of ore sources was carried out using well-known mineralogical and geochemical methods. All analyses were performed in the laboratory of physical-chemical methods of analysis of the Diamond and Precious Metal Geology Institute, SB RAS (DPMGI SB RAS), Yakutsk (Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Identified patterns made it possible to develop a method for predicting minerogenic types of gold deposits based on the indicators of placer gold and features of their distribution and to link them with various geological structures for the first time [15]. Similar studies on the mineralogy of placer gold, in order to identify the types of ore sources and the genesis of placers, have been successfully conducted and continue to be developed by Russian scientists [16][17][18][19][20][21][22] and also by foreign researchers [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The study of the typomorphic features of placer gold (morphology, chemical composition, micro-inclusions, internal structure) in order to identify minerogenic types of ore sources was carried out using well-known mineralogical and geochemical methods. All analyses were performed in the laboratory of physical-chemical methods of analysis of the Diamond and Precious Metal Geology Institute, SB RAS (DPMGI SB RAS), Yakutsk (Russia).…”
Section: Methodsmentioning
confidence: 99%
“…The Cu-Pd-Au diagram also shows two-phase areas at 350 and 550 • C surrounding the ordered phases of PdCu and AuCu, which according to [26] are in contact at 545 • C. Palladium alloying of gold-copper alloys increases the formation temperature of the AuCu compound. The article [44] describes in detail the associations of minerals of the Cu-Pd-Au system, their compositions, and conditions of formation in various types of gold deposits.…”
Section: Forms Of Intergrowths Of Pgm and Gold Their Interpretation O...mentioning
confidence: 99%
“…The review by Palyanova et al [11] summarized the available information on the palladian gold of several compositions and types of isomorphic impurities (Ag, Cu, Hg). The authors concluded that palladian gold more frequently corresponds to the Au-Pd-Ag, Au-Pd-Ag-Cu and Au-Pd-Ag-Cu-Hg systems and less often to Au-Pd, Au-Pd-Hg, Au-Pd-Cu, Au-Pd-Ag-Hg.…”
mentioning
confidence: 99%